SEXUAL PREFERENCE AND GROUP MEMBERSHIP ANALYSIS IN TURN-TAKING SYSTEM OF CASUAL CONVERSATIONS AMONG HOMOSEXUALS - agustina lestary (Jurnal Lingua Idea, 2016)
This research is aimed to investigate how sexual preference is displayed. The data of this study are casual conversation among homosexual men. The features of the turn-taking system analyzed is topic shift to determine the topics mostly discussed in the conversations. How the choices of the topic induce the in-group membership feeling among the participants will also be analyzed.. Qualitative approach, with inferential method, is used in this research. The result of this study shows that the most common topics brought by homosexual men during their conversations are relationship/dating, sexuality, dressing up, people and light topics. Furthermore, the sexual preference of the participants provides basic common ground for speakers to initiate the conversations and to develop sense of belonging